2019
DOI: 10.1007/s42452-019-0957-7
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of nanosheets attached nanotetrapods of zinc oxide

Abstract: A unique morphology of ZnO nanostructures namely nanosheets attached nanotetrapods have been grown using thermal evaporation of zinc, which promises innovative advantages of both one and two dimensional nanostructures. The nanostructures have been characterized using X-ray Diffractometer, Scanning Electron Microscope, Transmission Electron Microscope, Energy Dispersive X-ray Analysis and Photoluminescence (PL) techniques. Various effects of low dimensionality have been analysed. Indexing of various peaks in XR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The functional groups present in biomass filtrate have critical roles in the fabrication process of the nanoparticles. The Biosynthesized ZnONPs were added to a mesoporous silica (Santa Barbara-15, SBA-15) for the determination of acetaminophen in ETPG 16 ATSDPV 0.05-2.5 0.0025 [74] ZnONPs/SBA-15/GCE DPV 4-32 0.11 This work [1] poly (acid yellow 9), [2] glassy carbon electrode, [3] Functionalized multi-wall carbon nanotubes, [4] poly (3,4-ethylenedioxythiophene), [5] Graphene oxide, [6] Boron-doped diamond, [7] Gold nanoparticles, [8] Multi-walled carbon nanotubes, [9] Nickel oxide nanoparticles, [10] Carbon black, [11] Dihexadecylphosphate, [12] Laccase, [13] Carbon paste electrode, [14] 4-Hydroxyquinoline-3-carboxylic Acid, [15] Screen-printed electrodes, [16] Electroochemically treated pencil graphite, ATS: Adsorptive transfer stripping, SWV: Square wave voltammetry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional groups present in biomass filtrate have critical roles in the fabrication process of the nanoparticles. The Biosynthesized ZnONPs were added to a mesoporous silica (Santa Barbara-15, SBA-15) for the determination of acetaminophen in ETPG 16 ATSDPV 0.05-2.5 0.0025 [74] ZnONPs/SBA-15/GCE DPV 4-32 0.11 This work [1] poly (acid yellow 9), [2] glassy carbon electrode, [3] Functionalized multi-wall carbon nanotubes, [4] poly (3,4-ethylenedioxythiophene), [5] Graphene oxide, [6] Boron-doped diamond, [7] Gold nanoparticles, [8] Multi-walled carbon nanotubes, [9] Nickel oxide nanoparticles, [10] Carbon black, [11] Dihexadecylphosphate, [12] Laccase, [13] Carbon paste electrode, [14] 4-Hydroxyquinoline-3-carboxylic Acid, [15] Screen-printed electrodes, [16] Electroochemically treated pencil graphite, ATS: Adsorptive transfer stripping, SWV: Square wave voltammetry.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that they can act as reducing and stabilizing agents for the biosynthesis of nanoparticles, which constitute a novel method of synthesis without any toxic chemicals been used. [6] Among the sources, plant extracts are the cheapest one, which therefore will be used in this work. The target metallic nanoparticles to be synthesized in this work is the zinc oxide nanoparticles (ZnONPs) known to be multifunctional, non-toxic, biocompatible, low cost and ecofriendly materials.…”
Section: Introductionmentioning
confidence: 99%
“…Spherical shaped ZnO NPs with an average size 20 nm was synthesized using Punica granatum leaf extract and exhibited ~93% degradation efficiency for Coomassie brilliant blue R‐250 dye under exposure to sunlight for 180 min. [ 107 ] Similarly, ZnO NPs prepared from Acalypha indica leaf extract showed 96% degradation efficiency for MB under 90 min sunlight exposure. [ 108 ] Dhandapani et al reported the ureolytic bacteria assisted the preparation of ZnO nanostructure and studied its potential to decolorize different dyes.…”
Section: Zinc Oxide Nanostructures Enabled Photo‐degradation Of Dyesmentioning
confidence: 99%
“…CBB R-250 was initially developed for use in the textile industry but is now majorly used as a basis of stain for the detection of protein in gel electrophoresis in the field of analytical biochemistry. 4 Besides a number of useful applications, it poses some severe threats to human beings and other living organisms. It belongs to a class of organic compounds termed as triphenylmethane dyes that have been widely reported for mutagenic and teratogenic effects on living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…K. Singh et al employed green synthesized ZnO NPs for the photodegradation of CBB R-250, and achieved 93% degradation in 3 hours. 4 Venkata et al reported on 58.38% degradation of CBB R-250 in 90 minutes using CuO NPs. 15 N. Kaur et al evaluated the performance of NiO NPs for the photodegradation of CBB R-250 dye, which resulted in 95.7% degradation in 140 minutes.…”
Section: Introductionmentioning
confidence: 99%